A unified power converter for solar PV and energy storage in dc microgrids - Coelho, Sergio (2022)
This paper deals with the development and experimental validation of a unified power converter for application in dc microgrids, contemplating the inclusion of solar photovoltaic (PV) panels and energy storage systems (ESS), namely batteries. Considering the limitations presented by the current structure of the power grid, mostly highlighted by the accentuated integration of emerging technologies (ESS, renewables, electric vehicles, and electrical appliances that natively operate in dc), it is extremely pertinent to adopt new topologies, architectures, and paradigms. In particular, decentralized power systems, unified topologies, and correspondent control algorithms are representative of a new trend towards a reduction in the number of power converters. Thus, the developed solution is designed to operaSAVE-15te at a nominal power of 3.6 kW, with a switching frequency of 100 kHz, and in four operation modes concerning power flow: (i) solar PV panels to batteries (PV2B); (ii) solar PV panels to dc grid (PV2G); (iii) batteries to dc grid (B2G); (iv) dc grid to batteries (G2B). Moreover, a dual active bridge converter guarantees galvanic isolation, while two back-end dc–dc converters are responsible for interfacing solar PV panels and batteries. The experimental validation of the proposed unified power converter proves its application value to self-consumption production units.